Characterizing the macro and micro mechanical properties of scaffolds for rotator cuff repair - Smith, R; Zargar, N; Brown, C; Nagra, N; Dakin, S; Snelling, S; Hakimi, O; Carr, A (Elsevier, 2017)
Background Retearing after rotator cuff surgery is a major clinical problem. Numerous scaffolds are being used to try to reduce retear rates. However, few have demonstrated clinical efficacy.We hypothesize that this lack of efficacy is due to insufficient mechanical properties. Therefore, we compared the macro and nano/micro mechanical properties of 7 commercially available scaffolds to those of the human supraspinatus tendons, whose function they seek to restore. Methods The clinically approved scaffolds tested were X-Repair, LARS ligament, Poly-Tape, BioFiber, GraftJacket, Permacol, and Conexa. Fresh frozen cadaveric human supraspinatus tendon samples were used. Macro mechanical properties were determined through tensile testing and rheometry. Scanning probe microscopy and scanning electron microscopy were performed to assess properties of materials at the nano/microscale (morphology, Young modulus, loss tangent). Results None of the scaffolds tested adequately approximated both the macro and micro mechanical properties of human supraspinatus tendon. Macroscale mechanical properties were insufficient to restore load-bearing function. The best-performing scaffolds on the macroscale (X-Repair, LARS ligament) had poor nano/microscale properties. Scaffolds approximating tendon properties on the nano/microscale (BioFiber, biologic scaffolds) had poor macroscale properties. Conclusion Existing scaffolds failed to adequately approximate the mechanical properties of human supraspinatus tendons. Combining the macroscopic mechanical properties of a synthetic scaffold with the micro mechanical properties of biologic scaffold could better achieve this goal. Future work should focus on advancing techniques to create new scaffolds with more desirable mechanical properties. This may help improve outcomes for rotator cuff surgery patients.